Antibacterial Activity Test of Tempuyung Leaf Extract (Sonchus arvensis L.) Against Streptococcus pyogenes and Its Formulation in an Edible Film - Restu Rianingsih (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Pharyngitis, an upper respiratory tract infection commonly caused by Streptococcus pyogenes, remains a significant health concern. The growing problem of antibiotic resistance has driven researchers to explore alternative therapeutic options derived from natural sources. One promising candidate is the tempuyung leaf (Sonchus arvensis L.), which is rich in secondary metabolites known to possess antibacterial properties. This study investigated the antibacterial activity of tempuyung leaf ethanol extract against Streptococcus pyogenes and assessed its potential application in an edible film formulation. Extraction was performed using maceration with 96% ethanol, yielding 13.85% extract. Phytochemical screening confirmed the presence of flavonoids, polyphenols, tannins, quinones, and steroids. Antibacterial activity was evaluated through the disk diffusion method at extract concentrations ranging from 2% to 10%. The highest inhibition zone, measuring 65.53 mm, was recorded at the 10% concentration, indicating strong antibacterial potential. The extract was subsequently formulated into edible films at concentrations of 3%, 4%, and 5%, and subjected to physical quality evaluations covering organoleptic properties, pH, thickness, dissolution time, moisture content, and weight uniformity. Results showed that all formulations satisfied the standard requirements for most parameters, with the exception of weight uniformity, which did not yet meet established criteria. The edible film containing 5% extract demonstrated the greatest antibacterial activity, producing an inhibition zone of 27.12 mm, classified under the very strong category. These findings suggest that tempuyung leaf ethanol extract holds considerable promise as a natural antibacterial agent and may serve as an effective active ingredient in edible film preparations intended for managing pharyngitis caused by Streptococcus pyogenes.